New sciophilous sponges from the Caribbean (Porifera: Demospongiae) - van Soest, Rob W. M. (Zootaxa, 2009)
Thirteen new species of sponges are described from coral reefs of the Netherlands Antilles and the Colombian Caribbean. Species were collected during quantitative investigations of reef sponges performed by students of the University of Amsterdam in the period between 1984 and 1991. Most of the reported specimens were taken from undersides of coral rubble, crevices or reef caves (sciophilous habitats) and without exception are small encrusting or fistular sponges. The material reported in this paper includes a new genus and species of Placospongiidae, Placospherastra antillensis n. g. n. sp. , the first Caribbean representatives of the genera Triptolemma (Pachastrellidae) and Megaciella (Acarnidae), viz. Triptolemma endolithicum n. sp. and Megaciella incrustans n. sp., a new species of Timeidae, Timea curacaoensis n. sp., a new species of Microcionidae with peculiar colloscleres, Clathria (Thalysias) collosclera n. sp., two new species of Chondropsidae, viz. Batzella fusca n. sp., and Strongylacidon unguiferum n. sp., three new species of Coelosphaeridae, viz. Forcepia (Forcepia) minima n. sp., Forcepia (Forcepia) fistulosa n. sp., and Forcepia (Leptolabis) microlabis n. sp., a new species of Crellidae, Crella (Grayella) beglingerae n. sp., a new species of Hymedesmiidae, Hymedesmia (Hymedesmia) bonairensis n. sp., and a new species of Mycalidae, Mycale (Paresperella) vitellina n. sp. Most species are represented by only small fragments removed from the substrate by scalpel or diving knife, leaving little and often crumbled preserved type material. This study is intended to demonstrate that the small crusts dominating easily accessible shallow water coral rubble habitats in the Caribbean remain understudied.